Neurobiological basis of chiropractic manipulative treatment of the spine in the care of major depression - Kiani, Aysha Karim; Maltese, Paolo Enrico; Dautaj, Astrit; Paolacci, Stefano; Kurti, Danjela; Picotti, Pietro Maria; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: Major depressive disorder is associated with an autonomic nervous system imbalance. All the symptoms of depression (high cortisol, high adrenalin, insomnia, agitation, anxiety) can probably be attributed to over-activation of the sympathetic nervous system. We performed this review in order to highlight the possible links between chiropractic intervention, its potential molecular effects and its possible outcomes on patients with depression. Methods: We performed a literature search for all the relevant manuscript regarding the effects of chiropractic and depression on the autonomic nervous system. Results: Chiropractic care and spinal manipulation regulate the autonomic nervous system at peripheral level and its projections to the central nervous system. In particular, they may activate the parasympathetic system to counterbalance the activity of the sympathetic system. Vagal parasympathetic stimulation is also considered an effective therapy for major depression as it releases neurotrophins essential for anti-depressive therapies, including brain-derived neurotrophic factor and nerve growth factor. Conclusion: Chiropractic and spinal manipulative therapies along with vagal nerve stimulation may therefore be regarded as treatment options for depression.